A fourteen-faced hexangulaconulariid from the early Cambrian (Stage 2) Yanjiahe Formation, South China. (January 2020) - Guo, Junfeng; Han, Jian; Iten, Heyo Van; Wang, Xing; Qiang, Yaqin; Song, Zuchen; Wang, Wenzhe; Zhang, Zhifei; Li, Guoxiang
Abstract: Extant medusozoans (phylum Cnidaria) are dominated by forms showing tetraradial symmetry, but stem-group medusozoans of early Cambrian age collectively exhibit tetra-, bi-, penta-, and hexaradial symmetry. Moreover, the developmental and evolutionary relationships between four-fold and other types of radial symmetry in medusozoans remain poorly understood. Here we describe a new hexangulaconulariid, Septuconularia yanjiaheensis new genus new species, from Bed 5 of the Yanjiahe Formation (Cambrian Stage 2) in the Three Gorges area of Hupei Province, China. The laterally compressed, biradially symmetrical periderm of this species possesses 14 gently tapered faces, the most of any hexangulaconulariid described thus far. The faces are bordered by longitudinal ridges and crossed by short, irregularly spaced transverse ribs. Longitudinally, the periderm consists of three regions that probably correspond, respectively, to an embryonic stage, a transient juvenile stage, and a long adult stage. Septuconularia yanjiaheensis may have been derived from six-faced Hexaconularia (Fortunian Stage), which is morphologically intermediate between Septuconularia yanjiaheensis and Arthrochites . Furthermore, conulariids sensu stricto, carinachitids, and hexangulaconulariids may constitute a monophyletic group united by possession of an organic or organophosphatic periderm exhibiting longitudinal (corner) sulci, a facial midline, and offset of transverse ribs along the facial midline. UUID: http://zoobank.org/01a972aa-aef3-4eef-a9a5-c2d8c3dda615